Granny's Cottage by the Sea. The Role of Nostalgic Images in Conferring meaning to a Living Environment - Niemi, Anna (Ethnologia Fennica, 2001)
It is not important how the houses appear but what kind of emotions they evoke in the minds of those who not only observe them but live in them. (Nyman 1998, 159). There is a small group of cottages with saddle roofs on the seashore. Seeing the cottages from a far, you would think that they have been there for a hundred years. When you come closer, however, you can distinguish modern details, and up close you can tell that the cottages have been built out of new materials. Many Finns are fascinated by the country scenery, touched only by farmers working with their horses - a landscape without the large storehouses made of metal sheets and the bales wrapped in plastic in the fields. ln our dreams, the ideal place to live might just be in the countryside portrayed above, by a lake or by the sea. (TKU/TYKL. 5A&B, 13; TKU/TYKL. 1, 5.) Such scenery is part of many a Finn's past, but all that is left of it now are nostalgic memories. Well-preserved country scenery with its little red cottages is, to the Finns, often a symbol of the very core of being a Finn. The traditional landscape produces images of security and clarity in the minds of those who are used to seeing it.